Celastrol Suppresses Tumor Cell Growth through Targeting an AR-ERG-NF-κB Pathway in TMPRSS2/ERG Fusion Gene Expressing Prostate Cancer - Shao, Longjiang (Public Library of Science, 2013)
The TMPRSS2/ERG (T/E) fusion gene is present in the majority of all prostate cancers (PCa). We have shown previously that NF-kB signaling is highly activated in these T/E fusion expressing cells via phosphorylation of NF-kB p65 Ser536 (p536). We therefore hypothesize that targeting NF-kB signaling may be an efficacious approach for the subgroup of PCas that carry T/E fusions. Celastrol is a well known NF-kB inhibitor, and thus may inhibit T/E fusion expressing PCa cell growth. We therefore evaluated Celastrol’s effects in vitro and in vivo in VCaP cells, which express the T/E fusion gene. VCaP cells were treated with different concentrations of Celastrol and growth inhibition and target expression were evaluated. To test its ability to inhibit growth in vivo, 0.5 mg/kg Celastrol was used to treat mice bearing subcutaneous VCaP xenograft tumors. Our results show Celastrol can significantly inhibit the growth of T/E fusion expressing PCa cells both in vitro and in vivo through targeting three critical signaling pathways: AR, ERG and NF-kB in these cells. When mice received 0.5 mg/kg Celastrol for 4 times/week, significant growth inhibition was seen with no obvious toxicity or significant weight loss. Therefore, Celastrol is a promising candidate drug for T/E fusion expressing PCa. Our findings provide a novel strategy for the targeted therapy which may benefit the more than half of PCa patients who have T/E fusion expressing PCas.